Optimasi Jalur Pengangkutan Sampah pada TPS Kota Bandung Berbasis Sistem Informasi Geografis Menggunakan Algoritma Dijkstra - Fanny Assyifa (STMIK PPKIA Pradnya Paramita, 2026)
Urban waste management requires an effective transportation system, particularly in determining optimal routes from Temporary Waste Disposal Sites (TPS) to the Final Disposal Site (TPA). In Bandung City, waste transportation routes are generally determined manually based on drivers’ experience, which may lead to inefficient travel distances and increased operational time. This study aims to develop a Geographic Information System (GIS)-based route optimization system to identify efficient waste transportation routes. A quantitative descriptive approach was applied, supported by spatial analysis of TPS locations, TPA locations, and road network data. The Dijkstra algorithm was implemented within a spatial network analysis framework to calculate the shortest paths and estimate travel distances between locations. The system visualizes optimized routes through digital maps to support operational planning and decision-making. The results show that the proposed system produces shorter and more structured routes compared to conventional manual planning. Therefore, the developed GIS-based system can serve as a decision-support tool to improve the efficiency of urban waste transportation management in Bandung City.